Assessing the Effectivess of Electronic Technology on Record Management in Barangay Project 6 Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study was conducted to demonstrate the Assessing of Effectiveness of electronictechnology on record management in Barangay Project 6 Quezon City; the researchdetermined to provide knowledge to the readers about the importance and efficiency of usingelectronic technology and also to identify how the impact of electronic technologies help theemployee in record management. At the present time, technology has a great impact on ourdaily lives, not only in the office field but these technologies are also used when it comes tobusiness, organization, and communications.The researchers used qualitative instruments to examine the assessing the effectiveness ofelectronic technology on record management for every employee of Barangay Project 6Quezon City, and the proponents used the survey questionnaire and face-to-face interviewsas well as conducted almost an hour of discussion and gave the opportunity to therespondents to share more experience in using electronic technology.The respondents of this study are those who belong to Barangay Project 6 Staff, who arelimited to four respondents (4). The type of questionnaire used for interview questions will bein the form of Open-ended questions, which are answerable verbally. Upon proceeding toresults and discussion, the researcher found out the respondent's age profile is 21 to 30 yearsold and 51 above with the same count. The majority of the profile of respondents according toeducational attainment are college graduates and the majority profile of the respondentsaccording to Position is Admin Staff of Barangay.
Keywords: Business